2011
DOI: 10.1007/978-3-642-23217-6_32
|View full text |Cite
|
Sign up to set email alerts
|

The Complexity of Nash Equilibria in Limit-Average Games

Abstract: Abstract.We study the computational complexity of Nash equilibria in concurrent games with limit-average objectives. In particular, we prove that the existence of a Nash equilibrium in randomised strategies is undecidable, while the existence of a Nash equilibrium in pure strategies is decidable, even if we put a constraint on the payoff of the equilibrium. Our undecidability result holds even for a restricted class of concurrent games, where nonzero rewards occur only on terminal states. Moreover, we show tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 34 publications
1
64
0
Order By: Relevance
“…Relaxing any of these two design choices may lead to computational problems. Recent work on games has shown that allowing randomization, either in the strategies [31] or in the arenas [29] where the games are played may result in scenarios where computing the Nash equilibria of a game is undecidable, even for reachability objectives which can easily be expressed in LTL. However with respect to binary payoff sets, decidability can be recovered [30].…”
Section: Future Workmentioning
confidence: 99%
“…Relaxing any of these two design choices may lead to computational problems. Recent work on games has shown that allowing randomization, either in the strategies [31] or in the arenas [29] where the games are played may result in scenarios where computing the Nash equilibria of a game is undecidable, even for reachability objectives which can easily be expressed in LTL. However with respect to binary payoff sets, decidability can be recovered [30].…”
Section: Future Workmentioning
confidence: 99%
“…It is known that randomization, either in the strategies [37] or the arenas [36] can lead to undecidability; however, w.r.t. binary payoff sets, decidability can be recovered [35].…”
Section: Analysis and Related Workmentioning
confidence: 99%
“…Note that a pure Nash equilibrium is resistant to randomized strategies. On the other hand the existence of a randomized Nash equilibrium with a particular payoff is undecidable [12]. If the game contains a (pure) Nash equilibrium with some payoff payoff i for each player p i , then PRALINE returns at least one Nash equilibrium with payoff payoff i such that for every player p i , payoff i ≥ payoff i .…”
Section: Computing Nash Equilibriamentioning
confidence: 99%
“…There has recently been a lot of focus on the algorithmic aspect of Nash equilibria for games played on graphs [4,11,12]. Thanks to these efforts, the theoretical bases are understood well enough, so that we have developed effective algorithms [1,2].…”
Section: Introductionmentioning
confidence: 99%